2020
DOI: 10.1038/s41598-020-64146-6
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Dependent inductions of omega-3 and omega-6 polyunsaturated fatty acid metabolism act inversely on tumor progression

Abstract: The Western diet contains a high ratio of omega-6 (ω6) to omega-3 (ω3) polyunsaturated fatty acids (PUFA). The prototypical aryl hydrocarbon receptor (AHR) ligand, 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), induces CYP1 family enzymes, which can metabolize PUFA to epoxides. Mice fed ω3-rich or ω6-rich diets were treated with TCDD and injected subcutaneously with AHR-competent Hepa1-GFP hepatoma cells or AHR-deficient LLC lung cancer cells. TCDD reduced the growth rates of the resulting tumors in ω3-fed mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…These findings provided a ready explanation for the association between the AHR and cancer. That is, nominally “resting” AHR was seen to be activated by environmental chemicals to induce Phase 1 P450 hydroxylases that generate mutagenic intermediates from the pro-carcinogen parent compounds or from some endogenous substrates (e.g., estradiol or polyunsaturated fats [ 31 , 32 , 33 ]). These intermediates mutate DNA and initiate cancer.…”
Section: The First Hints Of a Role For The Ahr In Cancer: Carcinogmentioning
confidence: 99%
“…These findings provided a ready explanation for the association between the AHR and cancer. That is, nominally “resting” AHR was seen to be activated by environmental chemicals to induce Phase 1 P450 hydroxylases that generate mutagenic intermediates from the pro-carcinogen parent compounds or from some endogenous substrates (e.g., estradiol or polyunsaturated fats [ 31 , 32 , 33 ]). These intermediates mutate DNA and initiate cancer.…”
Section: The First Hints Of a Role For The Ahr In Cancer: Carcinogmentioning
confidence: 99%
“…Finally, how diet composition might interfere with the immune impact of AhR ligands is unknown. A recent study has shown that the AhR ligand TCDD reduced tumor growth in mice fed on an Omega-3 fatty acid-enriched diet while an Omega-6 fatty acid-enriched diet aggravated tumor growth [ 158 ]. While this study focused on the direct impact of AhR on tumor cells, the differential effect of AhR ligands on the Treg/Th17 balance depending on the dietary context cannot be excluded.…”
Section: Nutrient Sensing and Gut Immunometabolismmentioning
confidence: 99%
“…Particularly, it is well known that people following different diet regimes have different gut microbiome composition [ 158 ], and there is a correlation between high consumption of meat and fat with the risk to develop lung cancer [ 159 , 160 , 161 ]. For instance, it has been seen that specific metabolites such as omega-6 (ω6) polyunsaturated fatty acid (PF) and ω3PF can have opposite effect on cancer progression [ 162 ]. In fact, while ω6PF have been shown to induce pro-inflammatory phenotype increasing cancer progression, ω3PF have an anti-proliferative and apoptotic effect on different lung cancer cells [ 163 ].…”
Section: Microbiota and Lung Cancermentioning
confidence: 99%